Estudo da formação e remoção de tortas de filtração de gases em filtros de tecidos de polipropileno e de algodão - Rodrigues, Antonio Carlos Marques (2004)
The purpose of this work is to evaluate and to compare, in the processes of cake formation and remotion in the gases filtration with Bag Filters, the behavior of a filter made of natural fibers fabric with other made of synthetic fibers. The fabrics compared were a woven cotton with granite texture of 0.735 kg/m² and a non woven polypropylene of 0.600 kg/m². The experimental apparatus consisted of a circular filter with 0.023 m² in area, a powder feeder with controlled powder flow rate and humidity, linked with a microcomputer and a system to collect de data. The particle material was a phosphatic concentrated of density 2.79 x 10³ kg/m³ with mean particle diameter of 4.55 x 10-6 m. In the realization of this work, they were accomplished filtering procedures of the particle material in samples of the mentioned fabrics and cake remotion procedures with reverse air flow procedure, in order to determine the cake removing tension by the method proposed by Seville et al. (1989), also being evaluated other filtration and remotion aspects and data. In order to compare e evaluated the behavior of the fabrics in job conditions, they were also accomplished successive filtration and cleaning cycles in both fabrics until they become particle material saturated. During filtration four gas velocities were employed (4.5; 6.0; 7.5 and 9.0 cm/s), the flow rate was adjusted to 2.0 x 10-5 kg/s (11% of the feeder total velocity) and three maximum pressure drops across the filter were employed (300 mmH2O, 400 mmH2O and 500 mmH2O). In the cleaning steps six cleaning gas velocities were employed (1.6 cm/s; 3.0 cm/s; 9.0 cm/s; 12.0 cm/s; 15.0 cm/s and 18.0 cm/s). In the successive filtration and cleaning cycles they were employed gas filtration velocity of 6.0 cm/s, filtration final pressure drop of 400 mmH2O and gas cleaning velocity of 18.0 cm/s. The polypropylene fabric has taken more cycles to be saturated with the powder in the filtration and cleaning cycles and presented a greater cleaning degree in the cleaning processes, 77% in average, than the cotton that presented 39% of cake removal in average. The polypropylene fabric porosity was found to be greather than the cotton fabric ones. The cake-fabric adhesion force per unit of area has increased with the increase of the filtration gas velocity for both clothes, being remarkable that the polypropylene fabric has presented greather values than the cotton fabric, especially for the cakes formed with filtration gas velocities of 6.0 and 7.5 cm/s. It was also observed that the cake plaques, removed in the cleaning procedures, have increased in size with the increase of the cake removed portion and with the cake mass per unit of area for both studied fabrics.